Dynamic Simulation and Operating Characteristics of Ground-Coupled Heat Pump with Solar Seasonal Heat Storage System. Issue 9 (30th May 2020) - Lyu, Chao; Leong, Wey H.; Zheng, Maoyu; Jiang, Ping; Yu, Feng; Liu, Yueqin
Abstract: A hybrid ground-coupled heat pump (GCHP) is an efficient and sustainable technology for space heating and cooling. A demonstration house equipped with GCHP with a solar seasonal heat storage (SSHS) system had been built in Harbin, a severe cold zone of China. A dynamic simulation model was built for the house and GCHP with the SSHS system using TRNSYS. The model used a newly developed vertical ground heat exchanger (VGHE) module which considered coupled heat and moisture transfer (CHMT) in ground with variable soil properties (VSPs) and phase change of soil moisture (PCSM). In the simulation, a large amount of computing is consumed for VSP and PCSM, while the computing amount for moisture transfer is small. The model with the new VGHE module produced better simulated results, compared with the field data. So, CHMT-VSP-PCSM affects the performance of VGHE and system to some extent, especially CHMT. Hourly variation laws of temperatures and energy parameters were analyzed, and different characteristics were showed up at different operating stages in heating and cooling seasons for both long and short terms. The GCHP with the SSHS system can meet the heating and cooling demands of the house in general. In cooling season, adjusting the ratio of the two groups of VGHE for heat storage and cooling will increase the utilization efficiency of VGHE and make the soil temperature more balanced.